Primary amelanotic melanoma of anorectum – a rare case report with diagnostic challenge - Singh, Gyanendra; Singh, Anurag (Polish Journal of Pathology, 2023)
Anorectal melanoma is an exceptionally rare and aggressive form of cancer. One per cent of anorectal malignant tumours are anorectal malignant melanomas, which are exceedingly uncommon. We report a case of a 47-year-old woman who experienced painless rectal bleeding. On examination, an irregular lump was seen in the posterior rectal wall, measuring 4 × 3.7 cm. Biopsies were obtained under endoscopic guidance for histomorphology and immunohistochemistry. The biopsy examination showed nests of tumour mass in the lamina and muscularis mucosae. The tumour mass was composed of round to oval cells having enlarged nuclei, conspicuous nucleoli, and a scant amount of cytoplasm. No melanin pigmentation was noted in the tumour cells. HMB-45, S-100, and vimentin were all detected by immunohistochemistry. A definitive diagnosis of amelanotic malignant melanoma was rendered. The patient underwent abdominoperineal resection with a hysterectomy and bilateral salpingo-oophorectomy. Anorectal melanoma presents with bleeding per rectum and is often misdiagnosed as internal haemorrhoids or adenocarcinoma clinically. Amelanotic melanoma, which lacks melanin pigment, is difficult to diagnose. Patients who appear with rectal bleeding should have a malignant melanoma evaluation as a possible differential diagnosis, and suitable diagnostic procedures, such as a colonoscopy and a biopsy with immunohistochemistry, should be carried out to arrive at a conclusive diagnosis.